Identifying factors associated with the success and failure of terrestrial insect translocations. (August 2019) - Bellis, Joe; Bourke, David; Williams, Christopher; Dalrymple, Sarah
Abstract: Translocation is increasingly used as a management strategy to mitigate the effects of human activity on biodiversity. Based on the current literature, we summarised trends in terrestrial insect translocations and identified factors associated with success and failure. As the authors' definitions of success and failure varied according to the individual sets of goals and objectives in each project, we adopted a standardised species-specific definition of success. We applied generalised linear models and information-theoretic model selection to identify the most important factors associated with translocation success. We found literature documenting the translocation of 74 terrestrial insect species to 134 release sites. Of the translocations motivated by conservation, 52% were considered successful, 31% were considered to have failed and 17% were undetermined. Our results indicate that the number of individuals released at a translocation site was the most important factor associated with translocation success, despite this being a relatively infrequent perceived cause of failure as reported by authors. Factors relating to weather and climate and habitat quality were the most commonly perceived causes of translocation failure by authors. Consideration of these factors by managers during the planning process may increase the chance of success in future translocation attempts of terrestrial insects.